Perancangan dan Implementasi Sistem Pengajuan Keluhan Karyawan Berbasis Web - Andriyanto; Henny Dwi Bhakti (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The manual submission of employee complaints often leads to slow handling, disorganized documentation, and limited transparency regarding complaint progress. These issues hinder internal communication and reduce the effectiveness of administrative processes. This study aims to design and implement a Web-Based Employee Complaint Submission System using PHP and the Bootstrap framework to improve efficiency and accuracy in managing complaints. The system supports three main categories of complaints: payroll, occupational safety and health, and work facilities. It also enables employees to track complaint status through request, approved, and rejected indicators. Administrators can manage user accounts and generate official follow-up letters. Implementation results show that the system improves data recording, enhances documentation order, and increases transparency in complaint handling. Overall, the system facilitates more structured, efficient, and traceable communication between employees and management, supporting better corporate governance.